Biracial – Black? A Survey of Language Use and Attitudes in Poland and Germany - Pułaczewska, Hanna (Research in Language, 2013)
The paper deals with the construction of race from the perspective of cognitive sociolinguistics. The focus is upon the perception of mixed-race people of black and white heritage in Poland and Germany compared to the USA, and its reflection in language use. The study clarifies in how far a socially marked perception of biracial people applies in these countries with very small population of black ancestry. Among other things, the first presidential campaign of Barack Obama is used to investigate the occurrence in both countries of mental colouring of biracial people. The paper also reflects the language debate on political correctness of the press language, sparked off by the presidential campaign and its media coverage. It presents claims and arguments by proponents of various solutions regarding referring to biracial people, and paradoxes showing up in the relationship between language use and ideological positions when the race issue is at stake.